2007
DOI: 10.1037/0021-9010.92.3.722
|View full text |Cite
|
Sign up to set email alerts
|

An integrative typology of personality assessment for aggression: Implications for predicting counterproductive workplace behavior.

Abstract: This study presents an integrative typology of personality assessment for aggression. In this typology, self-report and conditional reasoning (L. R. James, 1998) methodologies are used to assess 2 separate, yet often congruent, components of aggressive personalities. Specifically, self-report is used to assess explicit components of aggressive tendencies, such as self-perceived aggression, whereas conditional reasoning is used to assess implicit components, in particular, the unconscious biases in reasoning th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
98
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 59 publications
2
98
0
4
Order By: Relevance
“…Consequently, research focusing on only one type of cognition to the exclusion of the other ultimately may lack the explanatory and predictive power that it would have obtained had both components of personality been considered. Thus, there is growing appreciation for the theoretical and practical value that both implicit and explicit social cognitions have in helping to explain behavior in experimental, social, and organizational contexts (Bing, Burroughs, Whanger, Green, & James, 2000;Brewin, 1989;Epstein, 1994;Greenwald & Banaji, 1995;Hogan, 1991;LeBreton et al, 2006;D. C. McClelland et al, 1989;Mischel & Shoda, 1995;Spangler, 1992;Westen, 1998;Winter et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, research focusing on only one type of cognition to the exclusion of the other ultimately may lack the explanatory and predictive power that it would have obtained had both components of personality been considered. Thus, there is growing appreciation for the theoretical and practical value that both implicit and explicit social cognitions have in helping to explain behavior in experimental, social, and organizational contexts (Bing, Burroughs, Whanger, Green, & James, 2000;Brewin, 1989;Epstein, 1994;Greenwald & Banaji, 1995;Hogan, 1991;LeBreton et al, 2006;D. C. McClelland et al, 1989;Mischel & Shoda, 1995;Spangler, 1992;Westen, 1998;Winter et al, 1998).…”
mentioning
confidence: 99%
“…Additionally, Winter et al (1998) have demonstrated that implicit affiliation motives interact with explicit affiliation motives (i.e., extraversion) in the prediction of interpersonal difficulties. In recent organizational research, implicit and explicit motives have been integrated to theoretically explain Csikszentmihalyi's (1975) flow experience (Kehr, 2004), and implicit and explicit aggressive cognitions have been integrated to empirically predict deviant workplace behavior, with the validity of self-reported explicit aggression varying across levels of implicit aggression as measured by conditional reasoning (e.g., Bing et al, 2000).…”
mentioning
confidence: 99%
“…The ''channeling hypothesis'' stipulates that implicit motives primarily influence behavior when explicit personality traits that facilitate their expression are present (McClelland, Koestner, & Weinberger, 1989). Such interactive effects have been observed using TAT and CRT measures of power and affiliation motives, as well as aggressive cognitions (Bing, Stewart, et al, 2007;Frost, Ko, & James, 2007;Winter, John, Stewart, Klohnen, & Duncan, 1998). For example, TAT measures of the implicit need for affiliation and power predicted future behaviors more effectively for extroverted than introverted participants (Winter et al, 1998).…”
Section: Moderator Effectsmentioning
confidence: 99%
“…Although many organizational scholars are likely familiar with some contemporary implicit measures, we believe that uncertainty about the appropriateness of their use, questions about start-up costs, misconceptions about their theoretical lineage, and mistaken assumptions about the domains 554 Organizational Research Methods 15(4) self-concept (Bing, Stewart, et al, 2007;Johnson & Saboe, 2011), beliefs (Reynolds et al, 2010), and affect , including both implicit and explicit measures yields better prediction and understanding of important work outcomes. With our criteria and recommendations in hand, scholars can readily respond to calls for research on implicit processes in organizations (e.g., Barsade, Ramarajan, & Westen, 2009;George, 2009;Latham, Stajkovic, & Locke, 2010).…”
mentioning
confidence: 99%
“…Research shows the added benefit of using an explicit measure and an implicit measure in combination to fully capture personality constructs (Bing, Stewart, Davison, Green, McIntyre, & James, 2007;Bing, LeBreton, Davison, Migetz, & James, 2007;Bornstein, 2002;James, 1998;Winter, John, Stewart, Klohnen, & Duncan, 1998). Selfreport measures of conscious (explicit) cognitions have a history of low and often nonsignificant correlations with various implicit, usually projective, measures (Greenwald & Banaji, 1995;McClelland, Koestner, & Weinberger, 1989;Nisbett & Wilson, 1977).…”
Section: Conditional Reasoning Tests or Crts This Psychometric Appromentioning
confidence: 99%